Perubahan gunatanah dan tahap kualiti air sungai di bandaraya Ipoh, Perak - Nasir Nayan; Mohmadisa Hashim; Mohd Hairy Ibrahim; Mohamad Suhaily Yusri Che Ngah (Environmental Management Society, Malaysia, 2009)
The background of this paper is based on the research conducted to investigate the landuse changes in Ipoh Metropolitant from the persepctive of time and spatial with the use of geographical information systems and other statistic softwares. The data used mainly secunder data called Ipoh landuse originated from Peninsular Malaysia Agriculture Depatment vary from the year of 1997, 2000, 2002 and 2004. At the same time other secunder data used is from Alam Sekitar Malaysia Sdn Bhd company for the year 2006. The result showed the changes are obvious for the urban and mining type of landuse for the eigth periodical year’s. Urban type of landuse detected increased 2 percent with the decresed of 3.75 percent of mining areas. The urban changes in this area indirectly impacted to the lower down the water quality especially in Sungai Kinta river basin. Based on the Water Quality Index’s, Sungai Kinta river basin are found to be at the moderate level for the water pollution. Apparently, the water quality level for parameter of BOD, COD, SS and NH3N showed the sign of extreme density at the middle of the study area known as Metropolitant Center of Ipoh. The changes of urbanization happend in outskirt of Ipoh has brough the sedimentation particels into Ipoh center through the main river channel Kinta River. The local authority especially Ipoh City Council will need to make more effective precaution measures in order to monitor the landuse changes occured in this area and the changes are not impacted the water quality supply in this riverbasin and to assure the highest quality of life for the people lives in this area. At the same time people also will need to play a role in order to lower down any kind of water pollution especially by controlling the domestic waste